Pengembangan Limbah Botol Plastik Untuk Aksesoris Make Up Karakter Luka Pada Siswa Sekolah Menengah Kejuruan Tata Kecantikan - Winda, Novia Restu Windayani; Maspiyah, Maspiyah; Biyan Yesi (Journal of Beauty and Cosmetology (JBC), 2021)
Learning in vocational school with a variety of subjects, one of which is character makeup is divided into two types, namely two-dimensional character makeup and three-dimensional character makeup. Two-dimensional character makeup is a makeup that can only be seen from the front, while the three-dimensional character makeup results can be seen from the front, side or top. In character makeup, plastic bottle waste can be recycled into various accessories, such as dentures, prosthetic eyes, and prosthetic fingers commonly applied with latex glue used in making wounds on character makeup. These accessories can be made by pour printing technique, namely by pouring melted plastic liquid into the mold that has been made and then colored. The purpose of the study is to know the validity of character makeup accessories from PET / PETE bottle waste materials and find out the feasibility of character makeup accessories by using PET / PETE bottle waste. Experimental research methods, Data retrieval techniques using sensory test assessment, favorite trial, clinical trial, documentation, observation. Analytical techniques use descriptive percentages. Based on the results of the assessment, the average resulting from sensory tests scored 90.00% finger wound accessories, 68.33% tooth injuries and 90.00% eye injuries were categorized as very feasible, fondness tests on eye wounds 75.56%, finger wounds 75.00%, dental wounds 71.02% with the category of very worthy Conclusions: Based on the results of sensory tests, fondness tests, that accessories make up wound characters using PET bottle waste are declared feasible. Keywords: development; plastic bottle waste; character makeup